Effect of Particle Size on the Performance of TiO2 Based Dye-Sensitized Solar Cells - Maurya I.C.; Senapati S.; Singh S.; Srivastava P.; Maiti P.; Bahadur L. (My University, 2025)
The performance of TiO2 based dye-sensitized solar cells (DSSCs) is largely influenced by the size of the TiO2 particles. In this work, different-sized TiO2 nanoparticles have been synthesized by a facile sol–gel technique using polyethylene glycol (PEG) as capping agent and its performance as the photoanode of DSSC with N719 sensitizer dye is investigated. Particle nature and dimension of TiO2 nanoparticles were studied through XRD, FTIR, SEM and dynamic light scattering (DLS) analyses, whereas thermal stability was investigated through TGA in the temperature range of 30–600 °C 30–600 °C. The DSSC assembled with photoanode consisted of smallest size TiO2 nanoparticles obtained using 3 mM PEG (TNP-II) exhibited solar-to-electrical energy conversion efficiency of 2.5%, under illumination of 100 mWcm−2, which was an extensive improvement compared to the device based on un-capped, TiO2 nanoparticles based cell (TNP) (1.0%). The enhancement in efficiency resulting from the reduction of particles size of TiO2 is attributed to enlarged band-gap, increased specific surface area & surface to volume ratio of the photoanode, greater dye loading and more interactions between anchoring groups of the dye and surface of TiO2.EIS measurements revealed that TNP-II photoanode–based cells exhibited faster electron transport, increased electron lifetime, higher charge collection efficiency and less recombination leading to better photovoltaic output. The work shows that developed TNP-II nanoparticles have good potential for application in photoenergy conversion devices. © 2018 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim